Strategi Pengembangan Wisata Manggasang di Desa Batu Tunggal Kecamatan Hantakan Kabupaten Hulu Sungai Tengah Provinsi Kalimantan Selatan - Shafa Azzahra; Ellyn Normelani; Rosalina Kumalawati; Ghinia Anastsia Muhtar (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
This study aims to analyze the internal and external factors influencing the development of Manggasang Tourism in Batu Tunggal Village, Hantakan District, Hulu Sungai Tengah Regency, and to formulate the most effective strategies to enhance its attractiveness and competitiveness among other tourist destinations in South Kalimantan. A qualitative method with a SWOT analysis approach was employed. Primary data were collected through field observations, semistructured interviews with tourism managers, local residents, and visitors, as well as visual documentation. Secondary data were obtained from local government reports, publications by the Central Bureau of Statistics (BPS), and relevant literature. The research results show that the internal factors of Manggasang Tourism received a total score of 2.89, consisting of strengths amounting to 2.00 and weaknesses of 0.89. The main advantage lies in the natural beauty that remains pristine and attractive photo spots, while the weaknesses include limited infrastructure and supporting facilities. The external factors recorded a total score of 2.95, with opportunities of 1.62 in the form of government policy support, social media promotion, and ecotourism trends, while threats of 1.33 include competition from other tourist destinations and extreme weather conditions. The SWOT analysis produced a strategic coordinate of (1.11; 0.29), placing Wisata Manggasang in Quadrant I, where a growth strategy is considered the most appropriate for future development. This strategy relies on leveraging internal strengths to seize external opportunities through sustainable improvement of facilities, promotion, and diversification of tourism services